Lemons - Savage, Melissa (Melissa D.) (A Yearling Book, 2018)
After her mother dies in 1975, ten-year-old Lemonade must live with her grandfather in a small town famous for Bigfoot sightings and soon becomes friends with Tobin, a quirky Bigfoot investigator.